2008
DOI: 10.1002/pits.20288
|View full text |Cite
|
Sign up to set email alerts
|

Attachment relationships and adolescents' life satisfaction: Some relationships matter more to girls than boys

Abstract: This study examined the extent to which the quality of parent and peer attachments related to early adolescents' life satisfaction (LS), whether peer attachment served as a mediator between parent attachment and LS, and potential gender differences. A total of 587 middle school students in grades 6 through 8 participated. Although both parent and peer attachment positively related to LS, parent attachment was the stronger unique predictor. There was no significant difference between males and females in levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
132
5
32

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(185 citation statements)
references
References 72 publications
16
132
5
32
Order By: Relevance
“…program. Based on previous research that highlights the importance of fostering interpersonal relationships when working with girls [10][11][12], it is plausible to suggest that fostering a sense of belonging may have contributed to the effectiveness of the Go Girls! program.…”
Section: Original Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…program. Based on previous research that highlights the importance of fostering interpersonal relationships when working with girls [10][11][12], it is plausible to suggest that fostering a sense of belonging may have contributed to the effectiveness of the Go Girls! program.…”
Section: Original Researchmentioning
confidence: 99%
“…been identified as an important factor to consider when developing programs to target adolescent girls' behaviors. For example, interpersonal connections have been highlighted as particularly important for overcoming the unique challenges faced by adolescent girls [10][11][12]. In particular, when girls experience positive connections to their school, peers, or important adults (e.g., teachers, mentors, etc.…”
mentioning
confidence: 99%
“…U skladu s rezultatima nekoliko studija (npr. Ma i Huebner, 2008.;Livazović, 2011. ), djevojke su izvještavale o većoj kvaliteti odnosa s vršnjacima.…”
Section: Raspravaunclassified
“…A study showed that the father attachment was more significantly related to social competence in various social situations (Ma & Huebner, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Reliability is the extent to which the results of the measurement can be trusted (Azwar, 1999). Reliability estimation technique used was the Cronbach's Alpha coefficient technique, with the following formula.…”
Section: Reliability Testmentioning
confidence: 99%